Proposal for the ergonomic design for the professors lounge at the Carchi State Polytechnic University - Enríquez López , Jonathan Armando; Peña Benítez , John Jairo (Tierra Infinita, 2020)
Ergonomics is one of the factors that influence the development of activities, so the investigation team considered as a research problem "the furniture in the professor workstations of the Faculty of Agricultural Industries and Environmental Sciences help with the ergonomics of professors". Based on this problem, the objective was to design the ideal furniture for the ergonomics of the professors. For this, we worked with all professors who were considered standing and sitting postures. We worked considering the 5th and 95th percentiles for the design of the furniture. And the resulting change with the regulations established by INEN for this purpose.